2016
DOI: 10.1016/j.molmet.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the endocannabinoid/CB1 receptor system for treating obesity in Prader–Willi syndrome

Abstract: ObjectiveExtreme obesity is a core phenotypic feature of Prader–Willi syndrome (PWS). Among numerous metabolic regulators, the endocannabinoid (eCB) system is critically involved in controlling feeding, body weight, and energy metabolism, and a globally acting cannabinoid-1 receptor (CB1R) blockade reverses obesity both in animals and humans. The first-in-class CB1R antagonist rimonabant proved effective in inducing weight loss in adults with PWS. However, it is no longer available for clinical use because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 61 publications
2
67
0
1
Order By: Relevance
“…Liver tissue was extracted as described previously (Knani et al, 2016) and its triglyceride content determined using EnzyChrom ™ Triglyceride Assay Kit (BioAssay Systems, CA).…”
Section: In Vivo Metabolic Effectsmentioning
confidence: 99%
“…Liver tissue was extracted as described previously (Knani et al, 2016) and its triglyceride content determined using EnzyChrom ™ Triglyceride Assay Kit (BioAssay Systems, CA).…”
Section: In Vivo Metabolic Effectsmentioning
confidence: 99%
“…This leptin resensitization was shown to be significantly correlated with the reductions in food intake and body weight, suggesting that JD5037 might exert its hypophagic and weight‐lowering effects via the reversal of leptin resistance. A similar study showed consistent anti‐obesity effects of JD5037 in a PWS mouse model, in which mice receiving 28‐day treatment with JD5037 displayed improvements in body weight, hyperphagia, and obesity‐associated metabolic parameters . The same study reported that there were increased concentrations of eCBs and CB1R in the hypothalamus of mice with PWS.…”
Section: Resultsmentioning
confidence: 57%
“…These elevations were associated with increased fat mass, reduced energy expenditure, and decreased voluntary activity observed in mouse models of PWS. The dysregulated eCB system identified in mouse models of PWS was further confirmed in humans; there were upregulated levels of 2‐arachidonoylglycerol and arachidonic acid in plasma of patients with PWS . Thus, eCB system dysregulation may be responsible, at least in part, for the hyperphagia and obesity of PWS.…”
Section: Resultsmentioning
confidence: 75%
“…The identity of these hypothetical factors is unknown, however. It is notable that a recent study found an abnormal increase in 2-arachidonoylglycerol (2-AG) system, which may contribute to hyperphagia and obesity in Magel2 -null mice [41]. Interestingly, the changes in OEA production found in Magel2 -null mice are markedly different from those seen in mice that are made obese either by exposure to a high-fat diet or by genetic deletion of leptin ( ob / ob mice).…”
Section: Discussionmentioning
confidence: 99%